Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/prs.0000000000002431
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Incisional Negative-Pressure Wound Therapy Prevent Mastectomy Flap Necrosis in Immediate Expander-Based Breast Reconstruction?

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…The overall rate of skin flap necrosis after mastectomy with reconstruction was 24.6% (30/122). This rate is higher than that found in other studies, but given the fact that DTI reconstruction is associated with a high skin flap necrosis rate, this result is consistent with previous results [2,3,8,25]. The rate of severe skin flap necrosis was 4.1% (5/122) in the entire patient population, which is also consistent with other study results [2].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall rate of skin flap necrosis after mastectomy with reconstruction was 24.6% (30/122). This rate is higher than that found in other studies, but given the fact that DTI reconstruction is associated with a high skin flap necrosis rate, this result is consistent with previous results [2,3,8,25]. The rate of severe skin flap necrosis was 4.1% (5/122) in the entire patient population, which is also consistent with other study results [2].…”
Section: Discussionsupporting
confidence: 92%
“…Implant-associated infections can result in prolonged antibiotic use, additional surgical treatment, and implant removal [7]. Therefore, the application of an NPWT device as a preventive or treatment option for mastectomy flap necrosis has been examined [8]. The results of these studies suggest that the use of such a device is an effective treatment strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incisional NPWT group had a lower overall complication rate, overall mastectomy f lap necrosis rate, and major mastectomy f lap necrosis than the conventional dressing group [59].…”
Section: Breast Surgerymentioning
confidence: 81%
“…10,11,13 Clinical studies have shown that incisional NPWT can help to reduce the complication rates in contaminated surgeries (sternal incisions and laparotomy incisions), surgeries involving artificial implants underneath the incision (hernia repair, vascular surgery, joint surgery), [28][29][30] and arthroplasty procedures. 31,32 Recently, incisional NPWT use on mastectomy flaps has reduced their necrosis rate in patients undergoing immediate implant-based breast reconstruction. 33 Higher on the reconstructive ladder, NPWT has shown great value when employed in skin grafting.…”
Section: Discussionmentioning
confidence: 99%